Inherited Thrombotic Thrombocytopenic Purpura (Upshaw Schulman Syndrome) as Differential Diagnosis to Neonatal Septicaemia with Disseminated Intravascular Coagulation – a Case Series - Lehmberg, Kai; Hassenpflug, Wolf A.; Klaassen, Ilka; Hillebrand, Georg; Oyen, Florian; Budde, Ulrich; Singer, Dominique; Schneppenheim, Reinhard (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
We report on 3 male neonates with hereditary ADAMTS13 deficiency (Upshaw Schulman syndrome, USS), the inherited form of thrombotic thrombocytopenic purpura (TTP). 2 presented shortly after birth with thrombocytopenia followed by microangiopathic Coombs-negative haemolytic anaemia. Both initially received antibiotic treatment for suspected infection-associated thrombocytopenia. In one patient’s brother, the first bout of incipient TTP did not occur before 6 months of age, despite the same genetic defect. ADAMTS13 activity was<5%, compound heterozygous mutations were found in all patients. USS constitutes a differential diagnosis to thrombocytopenia caused by disseminated intravascular coagulation in neonatal septicaemia. Administration of fresh frozen plasma usually resolves acute bouts of the disease. In some cases of thrombocytopenia of unknown origin in infancy, the resolution of signs and symptoms after infusion of plasma may point towards the diagnosis.
Keywords: Upshaw Schulman Syndrome; Thrombotic Thrombocytopenic Purpura; Neonatal Thrombocytopenia; Haemolytic Anaemia; Microangiopathy